Synthesis and Structural Studies of Some Transition Metal Complexes of 5- phenyl-1,3,4 — Oxadiazole-2- thioethyl Carbanate - Alias, M. F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
New complexes of cobalt (II). palladium (II). and platiniurn(H) with 5-phenyl- 1.3,4-oxadiazole-2- thioethylcarbanate (OXE) have been prepared and characterized by elemental analysis, 1R.L-V-Vis spectra. magnetic susceptipibility. and conductivity- measurements. Probable structures of the prepared complexes have been reported.